2014
DOI: 10.1136/oemed-2014-102362.232
|View full text |Cite
|
Sign up to set email alerts
|

0110 Cancer Mortality among Styrene and Fibreglass Exposed Workers in the Reinforced Plastic Boatbuilding Industry

Abstract: Objectives To evaluate the mortality experience among all workers (n = 3199) employed at a phosphate fertiliser plant in central Florida beginning 1953 and followed through 2005. Method All-cause, all-cancers, and cause-specific standardised mortality ratios (SMRs) were calculated with the U. S. population as referent. Lung cancer and leukaemia risks were further evaluated using conditional logistic regression. Employment duration was used as an exposure surrogate for dose-response analyses. Results The mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies have suggested a potential link between fiberglass exposure and mesothelioma in boat builders. 51 Since Saint Gobain appears to have continued ChemFab's production of fiberglass coated fabrics, and boatbuilding is prominent in New England towns, we suggest that case-control studies may be informative to assess potential causes for mesothelioma in these industries.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have suggested a potential link between fiberglass exposure and mesothelioma in boat builders. 51 Since Saint Gobain appears to have continued ChemFab's production of fiberglass coated fabrics, and boatbuilding is prominent in New England towns, we suggest that case-control studies may be informative to assess potential causes for mesothelioma in these industries.…”
Section: Discussionmentioning
confidence: 97%